Photonic Crystal and its Application as a Biosensor for the Early Detection of Cancerous Cells - Adoghe, Anthony U; Noma-Osaghae, Etinosa; Yabkwa, Rimamchika Israel (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The motivation for this paper is the strikingly sad statistics, obtained from various research bodies globally, regarding the effect of cancers on the global populace and the impact of current methods put in place for the early diagnosis of cancer. This paper is novel for many reasons. Primarily, it presents the use of an optical biosensor based on photonic crystal for cancer cell detection. This biosensor was recently developed as an ultra-compact biochemical sensor based on a 2D photonic crystal cavity known for altering its spectrum in proportion to minute changes in refractive index. Secondarily, The Finite Difference Time Domain (FDTD) and Plane Wave Expansion (PWE) techniques were applied to analyze the possibility of using photonic crystals as biosensors for the detection of cancer cells. The obtained resonant wavelength from the analysis of simulated results was 1.54964 µm and transmitted power obtained from the analysis was 51.9%. For the cancerous cell sample, The PC 12 Cell, the obtained resonant wavelength from analysis of the simulated results was 1.54964 µm and the transmitted power obtained from the analysis was 55.6%.